Indoor air quality : guide for facility managers - Bas, Ed, 1954- (ENVIROnetBASE., 2004)
This guide provides a comprehensive account of indoor air quality hazards, their sources, and appropriate solutions. Written in easy-to-understand, non-technical terms, it is designed to be used as both a ready reference and a training guide for facility managers. Each specific type of indoor air hazard is addressed, including allergens, asbestos, formaldehyde and VOCs, radon, tobacco smoke, legionellosis and related illnesses, carbon monoxide, multiple chemical sensitivity, and toxic mold. The basics of proper ventilation and the relationship of the HVAC system to indoor air quality are fully explained. Fundamental procedures for maintaining good air quality, including filtration, control of humidity and moisture, and duct cleaning are examined in detail. A full chapter is devoted to recent developments and procedures for controlling toxic mold. Case studies are also included.